Pengalaman Penumpang dalam Menggunakan Layanan dan Fasilitas Kereta Api (Studi Grounded Theory Penumpang Kereta Api Taksaka Hype Trip) - Nabila, Aliya Kafka (Magister of Communication Science, Sahid University Jakarta., 2025)
This study examines passengers' experiences with the Taksaka Hype Trip train services and facilities. Passengers'Â experiences vary when using the services and facilities on each train. Various factors contribute to a positive or negative passenger experience. This study aims to understand how passengers experience the Taksaka Hype Trip and the factors that influence it. This qualitative research employs Grounded theory. The data in this study are derived from in-depth interviews with several informants. The informants were selected based on the researcher's criteria to ensure that the data obtained are relevant to the research objectives. The results of this study explain that passengers' experiences, whether positive or negative, can shape their perceptions and loyalty, influenced by situational factors.